Pengaruh Literasi Keuangan, Preferensi Risiko, dan Influencer Media Sosial Terhadap Minat Investasi Generasi Milenial (Studi Pada Anggota IPNU & IPPNU Tingkat Kecamatan Bangsri) - Safitri, Novita Ayu; Wibowo, Purwo Adi (Oikonomia: Jurnal Manajemen, 2025)
Purpose The purpose of this research is to find out how the influence given by financial literacy, risk preferences and social media influencers on millennial generation investment interest in IPNU & IPPNU members at the Bangsri District Level. Methodology, this research is a type of quantitative research (Primary Data), where the data is obtained from a questionnaire distributed via Google Form. IPNU & IPPNU members at the Bangsri District Level with a total of 1,500 people constitute the research population. To determine the sample, purposive sampling technique was used which then resulted in a sample of 106 respondents. The data obtained were then analyzed using the multiple linear regression analysis method using the help of the IBM SPSS Statistic 25 program. Findings, The findings obtained from this study indicate a significant positive effect of financial literacy and social media influencers on millennial generation investment interest. Meanwhile, risk preference does not show its influence on millennials' investment interest. Suggestions before investing investors must understand the financial basis they have and the risks of investing.